Effect of Insulin on Expression of LDLR, SREBP-2 and Cell Proliferation in Chang (normal) Liver Cells - Nimai C. Chandra 2*Hemlata Pandey 1, Veena Pande 1 (Journal of Biomedical and Pharmaceutical Research, 2017)
Low-density lipoprotein receptor (LDLR) maintains lipid metabolism and its expression is regulated by Sterol Regulatory Element Binding proteins (SREBPs). This study was designed to investigate the effect of insulin, a mitogen on LDLR, SREBP-2 receptor expression and cell proliferation. Insulin was found to have a stimulatory effect on the expression of LDLR and its transcription factor SREBP-2. Fluorescent dye (Dil) labelling assay revealed significantly increased uptake of Dil-LDL in the presence of insulin. Insulin also showed increased rate of cell replication. These findings suggested that LDLR expression is enhanced in the presence of insulin, which in turn results in increased uptake of LDL into the cells causing increased cell proliferation. The elevated expression of SREBP-2 indicated the influence of insulin on the transcription of genes responsible for increased expression and activity of LDLR. Keywords: LDL receptor, SREBP-2, Atherosclerosis, LDL uptake and BrdU Assay.